2023
DOI: 10.1371/journal.pone.0289631
|View full text |Cite
|
Sign up to set email alerts
|

Associations of eccentric force variables during jumping and eccentric lower-limb strength with vertical jump performance: A systematic review

Abstract: The purpose of this systematic review was to summarize the associations of eccentric force variables during jumping and eccentric lower-limb strength with vertical jump performance. A literature search was conducted in September 2022 using PubMed, Web of Science, and Scopus. Thirteen cross-sectional studies investigating the relationship between eccentric force and strength variables, such as force, rate of force development (RFD), power, time, and velocity, and vertical jump performance, including the jump he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Previous studies have indicated that increased eccentric muscle forces play a role in enhancing vertical jump height. 46 This is attributed to the correlation between eccentric strength during knee extension and squatting exercises and the resulting jump height. Consequently, an augmentation in jump height might be attributed to increased muscle forces and, subsequently, elevated loading at the joints.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that increased eccentric muscle forces play a role in enhancing vertical jump height. 46 This is attributed to the correlation between eccentric strength during knee extension and squatting exercises and the resulting jump height. Consequently, an augmentation in jump height might be attributed to increased muscle forces and, subsequently, elevated loading at the joints.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in the current study, a significant correlation between horizontal jumping abilities and the RSS was detected, representing 15% of the shared variance. This phenomenon may be partially due to the specific form of jumps administered, namely the SLJ, although it is acknowledged that the contribution of the stretch-shorteningcycle (SSC) to the initial phase of a sprint or jump is deemed to be minimal 66,67 .…”
Section: Discussionmentioning
confidence: 99%
“…SJ is a complex motor skill that requires complex motor coordination involving multiple joints but also requires perfect organization of motor behavior between the upper and lower body; no cognitive abilities are required. The height achieved in the SJ, both for inactive individuals and elite athletes, is indicative of explosive muscle strength and correlates with performance attributes like speed, agility, and power [ 21 ].…”
Section: Introductionmentioning
confidence: 99%